2014
DOI: 10.3109/10826084.2014.880722
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Suicidal Ideation Predict Successful Completion of Substance Abuse Treatment in a Criminal Justice Sample

Abstract: The goal of this study was to identify predictors of successful substance abuse treatment in an out-patient clinic for individuals being monitored under community corrections supervision. Of the 615 participants, 117 (19%) successfully completed treatment. The results of a multivariate logistic regression analysis indicated that successful treatment was associated with several baseline characteristics including: older age, White race, having greater than a high school education, lower level of care, meeting cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is not easy to correlate low educational level with poor outcome. It is known that, in SUD patients, successful treatment was associated with several baseline characteristics including older age, white race, having more than a high school education, lower level of care and not having a history of opioid use [ 32 ]. It is also true that, at first sight, control patients seem to be a more seriously ill control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is not easy to correlate low educational level with poor outcome. It is known that, in SUD patients, successful treatment was associated with several baseline characteristics including older age, white race, having more than a high school education, lower level of care and not having a history of opioid use [ 32 ]. It is also true that, at first sight, control patients seem to be a more seriously ill control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, established findings on substance use do not always generalize to criminal justice samples. For example, several studies examining community corrections samples have indicated that more severe substance use (i.e., use of more addictive and damaging substances) may not be associated with more severe outcomes (Clark et al, 2014; Listwan et al, 2009; Shaffer et al, 2011). The current study largely supported this pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated worse outcomes for harder substances in some cases (Clark et al, 2013) while in others no differences have been found. For example, recidivism rates in community corrections samples have shown no differences for crack cocaine use when compared to alcohol and marijuana use (Clark, Hendricks, Brown, & Cropsey, 2014; Shaffer, Hartman, Listwan, Howell, & Latessa, 2011), nor were differences found for methamphetamine users (crystal meth) when compared to non-meth users (72% of the comparison group was made up of alcohol and marijuana users; Listwan, Shaffer, & Hartman, 2009). Several possible explanations exist to explain this discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…Family plays a dominate role in their lives and because of this, members of the criminal justice system may have less resilience to recover from family conflict as opposed to other forms of setback. Mental illness and other forms of distress can be difficult to assess in this population (Clark, Hendricks, Brown, & Cropsey, 2014). The relationship between family conflict and suicide should be the object of future study as this is a marker for suicidality that members of the criminal justice system may be more likely to admit to.…”
Section: Discussionmentioning
confidence: 99%
“…First, self-report of family dysfunction as well as self-report of physical symptoms appear to be markers for suicide risk in the community corrections population. There is evidence that assessment of mental health symptoms (a traditional marker of suicide risk) can be difficult in this population (Clark et al, 2014). If a member of the community corrections population reports family dysfunction or physical symptoms then psychological distress and suicidal ideation should be assessed.…”
Section: Discussionmentioning
confidence: 99%